Zunanjetrgovinska politika v državah BRIICS - Koleša, Sabina (Naše gospodarstvo, 2010)
This article focuses on a group of emerging economies - namely, Brazil, Russia, India, Indonesia, China, and South Africa (BRIICS) - that have become important economic players in the last two decades. These countries have become increasingly open to world trade (liberalising trade and foreign direct investments), consequently reshaping global trade markets and the architecture of global trade relations. The article also analyses BRIICS'' trade policy response to the global economic and financial crisis (e.g., whether their trade policies shifted to protectionism) and the importance of trade relations between BRIICS and the EU (including Slovenia).
Keywords: zunanja trgovina; zunanjetrgovinsko poslovanje; liberalizacija; globalizacija; globalization